Efektivitas Pembelajaran Menyimak Dongeng Berbasis Youtube Dalam Pembelajaran Bahasa Dan Budaya Sunda - Suchyadi, Yudhie; Indriani, Rini Sri; Budiana, Sandi; Martha, Layung Paramesti; Nurjanah, Nurjanah; Yusup, Muthia Khairunnisa Putri (Universitas Pakuan, 2024)
THE EFFECTIVENESS OF YOUTUBE-BASED FAIRY TALE LISTENING LEARNING IN SUNDANESE LANGUAGE AND CULTURE LEARNING Abstract. Sundanese fairy tales are part of Indonesian oral tradition and literature that are told by word of mouth so that they have the advantage of being delivered in everyday language so that listeners understand what is being conveyed better. However, on the other hand, the quality of the storyteller's understanding of the content, meaning, and interpretation of fairy tales can be reduced because of their oral nature. Fairy tale listeners as an important part of the oral tradition also experience changes in orientation due to technology and generational shifts, including in Sundanese families. So, if this condition is left unchecked, it is not impossible that oral fairy tale literature will lose its supporters and eventually become extinct. Information technology, especially mobile communication technology, is an inseparable part of the society that supports this fairy tale literature. This rapid technological development, including tablet computers, can be used as an opportunity to make efforts to revitalize fairy tale culture in the next generation of supporters. This research is motivated by the lack of knowledge of students in listening to fairy tales in the Sundanese Language and Culture Learning course. Therefore, this study aims to examine students' ability to listen to fairy tales effectively on YouTube media in the Sundanese Language and Culture Learning course. This research uses a quantitative approach. The method used is an experimental method with a pre-test and post-test design. The data source in the study was students who taught the Sundanese Language and Culture Learning course, totaling 68 students. The Technology Readiness Level states relevant facts and basic arguments ready to support the need for this study. The hypothesis, initial support, RD design to be carried out have been explored, then the methodology, procedures and stages to be carried out have been explored. This study was designed with the adequacy and completeness of the data to be determined, with technical evaluation and prediction of the results to be carried out. The results of the study can be concluded into several things: The ability to listen to stories of PGSD students before using YouTube media was less than satisfactory. Because of the 68 students who had just understood the contents of the fairy tale, only 10.68% listened, so a study was conducted using YouTube media in order to improve the value in learning to listen to fairy tales. After using YouTube media, the ability to listen to fairy tales of students from 68 students who understood the contents of the fairy tales they had listened to was 44.82%. So the influence of YouTube media on the ability to listen to fairy tales of PGSD students on the learning outcomes of listening to fairy tales before and after using YouTube media can improve the ability to listen to fairy tales.